Addressing Social Determinants of Health in the Care of Patients With Heart Failure: A Scientific Statement From the American Heart Association. Issue 22 (2nd June 2020) - White-Williams, Connie; Rossi, Laura P.; Bittner, Vera A.; Driscoll, Andrea; Durant, Raegan W.; Granger, Bradi B.; Graven, Lucinda J.; Kitko, Lisa; Newlin, Kim; Shirey, Maria
Abstract : Heart failure is a clinical syndrome that affects >6.5 million Americans, with an estimated 550 000 new cases diagnosed each year. The complexity of heart failure management is compounded by the number of patients who experience adverse downstream effects of the social determinants of health (SDOH). These patients are less able to access care and more likely to experience poor heart failure outcomes over time. Many patients face additional challenges associated with the cost of complex, chronic illness management and must make difficult decisions about their own health, particularly when the costs of medications and healthcare appointments are at odds with basic food and housing needs. This scientific statement summarizes the SDOH and the current state of knowledge important to understanding their impact on patients with heart failure. Specifically, this document includes a definition of SDOH, provider competencies, and SDOH assessment tools and addresses the following questions: (1) What models or frameworks guide healthcare providers to address SDOH? (2) What are the SDOH affecting the delivery of care and the interventions addressing them that affect the care and outcomes of patients with heart failure? (3) What are the opportunities for healthcare providers to address the SDOH affecting the care of patients with heart failure? We also include a case study (Data Supplement) that highlights an interprofessional team effort to address and mitigate the effects of SDOH in an underserved patient with heart failure. Abstract : Supplemental Digital Content is available in the text.